Karakteristik Pasien Otitis Media Akut di RSUD Sanjiwani Gianyar Tahun 2021 - Komang Vitri Apriliasari Apriliasari; Pande Ayu Naya Kasih Permatananda; Pt Amelia Agustini Siadja (Aesculapius Medical Journal, 2024)
[Characteristics of Acute Otitis Media Patients at The Regional Public Hospital Gianyar in 2021] Acute otitis media (AOM) is an acute infection of the middle ear mucosa caused by a virus or bacterial infection of the upper respiratory tract resulting in obstruction of the eustachian tube. Indonesia is ranked fourth as the country with the highest prevalence of ear disease (4.6%) in Southeast Asia. The purpose of this study was to determine the characteristics of acute otitis media patients at the Regional public Hospital Gianyar in 2021. The design used in this study was descriptive with a cross-sectional approach. The research was conducted at the ENT-HNS Polyclinic in Regional public Hospital Gianyar. The results obtained in this study are 48 patients who met the inclusion and exclusion criteria. So that some characteristics of AOM patients at Regional public Hospital Gianyar, including demographic characteristics are 47.9% aged 18-65 years and 66.6% were male, clinical characteristics, are 75% suffered from hyperemic stage and experienced ear pain and therapeutic characteristics, are 93,7 % of patients received medical therapy with a type of therapy dominated by antibiotics (95.8%).